2001
DOI: 10.1002/aic.690471118
|View full text |Cite
|
Sign up to set email alerts
|

Removal of surface adhered particles by surfactants and fluid motions

Abstract: Remo®ing or detaching particles from a surface is of interest in filter bed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…DLVO and lift forces) are related to forces directed parallel to the surface. However, in similar detachment studies it was found that lift forces are negligible and surface roughness may play a decisive role in determining the hydrodynamic force to remove adhering particles from the surface (Batra et al, 2001;Yiantsios & Karabelas, 1995). This feature is not accounted for in the DLVO theory.…”
Section: Discussionmentioning
confidence: 98%
“…DLVO and lift forces) are related to forces directed parallel to the surface. However, in similar detachment studies it was found that lift forces are negligible and surface roughness may play a decisive role in determining the hydrodynamic force to remove adhering particles from the surface (Batra et al, 2001;Yiantsios & Karabelas, 1995). This feature is not accounted for in the DLVO theory.…”
Section: Discussionmentioning
confidence: 98%
“…For two spheres of radius and pressed together under a load the radius of the circle of contact is given by: (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) where and are the elastic constants of the material of the spheres:…”
Section: Fig24 Two Spherical Particles In Contactmentioning
confidence: 99%
“…Adhesion forces between particles and surfaces, i.e. the force necessary to detach a particle from a surface is of interest in several industrial applications such as detergency [2], particle filtration [3] and petroleum production [4,5]. For biological systems such as cells or viruses, adhesion to surfaces is important for processes like biofilm formation or infection.…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the abundance of mobilized particles and the size of the mobilized particles both increased with increasing flow rate during the rainfall simulation, as expected from hydrodynamic detachment theory. Batra et al (2001) found that the hydrodynamic force for detachment theoretically increased as the surface asperity size approached the separation distance.…”
Section: Figures 4 Andmentioning
confidence: 99%